2013
DOI: 10.1590/s0365-05962013000200014
|View full text |Cite
|
Sign up to set email alerts
|

Rosai-Dorfman disease presenting with extensive cutaneous manifestation - Case report

Abstract: Rosai-Dorfman disease is a benign, self-limited, idiopathic proliferative histiocytic disorder. It was first described in 1969 by Rosai and Dorfman. In its typical form the disease is characterized by extensive cervical lymphadenopathy associated with fever, polyclonal gammopathy and leukocytosis with neutrophilia. The skin is the most common site affected. Extranodal manifestations have been reported in 43% of cases. In this study, we report an atypical case of Rosai-Dorfman disease in a female with massive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…3 Rarely, CRDD can present with pustules, acneiform lesions, panniculitis-or vasculitis-like lesions, macular erythema, annular lesions, breast tumors, or resemble vascular lesions. 3,[18][19][20] Ulcerative nodules, as seen in our patient, are unusual. We believe that this atypical presentation may be due to the fact that some lesions were located in previous chickenpox scars, which could have weakened the underlying tissue, allowing ulceration.…”
Section: Case Reportsupporting
confidence: 52%
See 2 more Smart Citations
“…3 Rarely, CRDD can present with pustules, acneiform lesions, panniculitis-or vasculitis-like lesions, macular erythema, annular lesions, breast tumors, or resemble vascular lesions. 3,[18][19][20] Ulcerative nodules, as seen in our patient, are unusual. We believe that this atypical presentation may be due to the fact that some lesions were located in previous chickenpox scars, which could have weakened the underlying tissue, allowing ulceration.…”
Section: Case Reportsupporting
confidence: 52%
“…Solitary or multiple erythematous‐brown to yellow papules, nodules, or plaques usually affecting the face (eyelids and malar region), back, anterior chest, thighs, abdomen, and shoulders are most frequently described 3 . Rarely, CRDD can present with pustules, acneiform lesions, panniculitis‐ or vasculitis‐like lesions, macular erythema, annular lesions, breast tumors, or resemble vascular lesions 3,18–20 . Ulcerative nodules, as seen in our patient, are unusual.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…6 RDD has mainly been reported in childhood and young adults in the second and third decade of life. 7 Constitutional symptoms are generally absent in the patients with CNS involvement. Neurological symptoms vary depending on the size, location and number of lesions; seizure and headache are the most common complaint in RDD patients.…”
Section: Rddmentioning
confidence: 99%
“…The main causes for RDD remain uncertain, however, its association with viral (such as human herpes virus 6 and Epstein-Barr virus infections) and immune causes have been suggested (Gaul & Chang, 2019). In the classic pattern, affected patients manifest with bilateral cervical lymphadenopathy and frequently with intermittent fevers, night sweats, and weight loss (di Dio et al, 2016;Fang & Chen, 2015;Leal et al, 2013) which did not treat with thalidomide but later responded to methotrexate (Nadal, Kervarrec, Machet, Petrella, & Machet, 2015). Numerous cases of cutaneous RDD have been reported that their lesions were solitary without good response to treatment (Fang & Chen, 2015;Nadal et al, 2015;Sun, Shi, Su, Zhang, & Lu, 2018).…”
Section: Discussionmentioning
confidence: 99%